KEKUATAN RESOLUSI MAJELIS UMUM PBB (UNGA) DAN DEWAN KEAMANAN PBB (UNSC) SEBAGAI SUMBER HUKUM INTERNASIONAL - Leovaldi Tirta (Fakultas Hukum Universitas Surabaya, 2018)
United Nations General Assembly (UNGA) Resolution as a declaration will be transformed into an international customary that has binding legal force as like other sources of international law. This process is called the 'instant customary of law'. Decisions of the United Nations Security Council (UNSC) have legally binding force based on Article 25 of the Charter. Its decisions have an impact for a country in conflict or dispute to comply and implement so for those states that violate will be given a sanction as regulated in the UN Charter.